2004
DOI: 10.1051/0004-6361:20041066
|View full text |Cite
|
Sign up to set email alerts
|

Polarization properties of broad absorption line QSOs: New statistical clues

Abstract: Abstract.We report the results of several statistical tests performed on a large sample of 139 broad absorption line (BAL) QSOs with good quality optical spectra and/or optical polarization data. Correlations between ten optical indices and the polarization degree p 0 are systematically searched for. We find six significant non-trivial correlations. In order to identify the most important correlations, we perform a principal component analysis with a sample of 30 BAL QSOs and eight quantities (including p 0 ).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 71 publications
8
61
1
Order By: Relevance
“…Goodrich & Miller 1995;Lamy & Hutsemékers 2004) provide additional evidence favoring this kind of scenario. First, the polarization angle rotates within the absorption line profiles, suggesting the existence of at least two sources and/or mechanisms of polarization.…”
Section: Consequences For the Bal Formationmentioning
confidence: 87%
See 2 more Smart Citations
“…Goodrich & Miller 1995;Lamy & Hutsemékers 2004) provide additional evidence favoring this kind of scenario. First, the polarization angle rotates within the absorption line profiles, suggesting the existence of at least two sources and/or mechanisms of polarization.…”
Section: Consequences For the Bal Formationmentioning
confidence: 87%
“…First, the polarization angle rotates within the absorption line profiles, suggesting the existence of at least two sources and/or mechanisms of polarization. The polar outflow and the disk, expected to produce perpendicular polarizations, can play this role, especially in the case of BAL QSOs with P Cygni-type profiles (Goodrich 1997;Hutsemékers et al 1998;Lamy & Hutsemékers 2004). Furthermore, the absorption in the polarized spectrum is clearly narrower than the absorption in the direct spectrum (this is best observed in Fig.…”
Section: Consequences For the Bal Formationmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, Wang et al (2010) summarised the observational evidence which implies that indeed the N v line is generally strongly contaminated by the resonance scattering of Lyα photons. Strong support is provided by the 10% polarisation fraction of the N v emission line (Lamy & Hutsemékers 2004), while the finding that other broad emission lines are unpolarised indicates that at least part of the emission is scattered light. Furthermore, Weymann et al (1991) found a difference between the strength of the N v line in BAL and non-BALQSOs, with excess N v emission extending to 10 000 km s −1 , much broader than the broad emission lines.…”
Section: Abundances From Broad Emission Linesmentioning
confidence: 95%
“…It was conceded, however, that this would require a very precise lensing configuration. Furthermore, the polarisation for the summed images has been seen to vary in the blue wing of the C IV λ1549 emission line, with fluctuations between ∼10% (Lamy & Hutsemékers 2004) and ∼20% (Schmidt & Hines 1999). Interestingly, these studies also found that continuum polarisation near the C IV feature was ∼2%, indicating some polarisation is still occurring away from the absorption troughs (Wang, Wang, & Wang 2005).…”
Section: H1413+1143mentioning
confidence: 87%